Some aspects of DNA analysis in the selection of small ruminants - Caro-Petrović Violeta (Institute for Animal Husbandry, Belgrade, 2021)
DNA analysis can have great practical application in the management and successful operation of the farm. The application of DNA technology is becoming a tremendous challenge for farm breeding of domestic animals. In recent years, traditional selection methods have been supplement by the results of molecular analysis of the genome. Determining the genetic distance of sheep and goat breeds had practical and multiple significance. Microsatellites are used widely in the selection, and genomic selection is becoming an increasing challenge for breeders. The development of SNP chips brings an immense advanced for rapid and comprehensive analysis of the genome, which is of great importance for the successful selection and Genomic selection in sheep concentrated on all aspects of genetic and production directions. However, it should be noted that genomic selections in sheep breeding, and especially in goat breeding, take place at a slower pace compared to cattle breeding.